Internet connectivity disruption in Egypt (Egypt) - Voidly (2026)
CRITICAL severity mixed detected in Egypt. Confidence: 67%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: EG-2026-0125
Keywords: censorship; EG; mixed; critical